2016
DOI: 10.1039/c6tc02924h
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly and mechanochromic luminescence switching of trifluoromethyl substituted 1,3,4-oxadiazole derivatives

Abstract: Stimuli responsive luminescence switching, liquid crystalline and gelation properties of 1,3,4-oxadiazole derivatives were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 113 publications
0
14
0
Order By: Relevance
“…This indicates that the reorganization process that occurs over time at room temperature is basically the same as induced by annealing: the annealing treatment simply accelerates this process. The observed blue‐shift of the absorption spectrum of T2CAO , even in comparison to the spectrum of the molecule in THF solution (Figure S6), indicates a progressive ordering in H‐aggregates induced by increasing temperature, which is further corroborated by the progressive decrease in the intensity of the emission band with temperature and the enormous apparent Stokes‐shift.…”
Section: Resultsmentioning
confidence: 69%
“…This indicates that the reorganization process that occurs over time at room temperature is basically the same as induced by annealing: the annealing treatment simply accelerates this process. The observed blue‐shift of the absorption spectrum of T2CAO , even in comparison to the spectrum of the molecule in THF solution (Figure S6), indicates a progressive ordering in H‐aggregates induced by increasing temperature, which is further corroborated by the progressive decrease in the intensity of the emission band with temperature and the enormous apparent Stokes‐shift.…”
Section: Resultsmentioning
confidence: 69%
“…The PL spectrum and fluorescence lifetime changes are shown in Figure 3a and 3b, respectively. It has been reported that materials whose color changed by gelation retained their luminescent color even in xerogels after the solvent was removed and showed a grinding response [26]. The powder in its initial state exhibited blue luminescence and no response to grinding.…”
Section: Resultsmentioning
confidence: 99%
“…Material applications of 1,3,4-oxadiazole derivatives lie in several areas. They can be used as photosensitizers, [24] liquid crystals, [25][26][27] luminescent materials, [28][29][30] electron-transport materials, [31,32] polymers, [33,34] herbicides [35] and corrosion inhibitors. [36,37] Thanks to their high therapeutic importance and material applications, a number of 1,3,4-oxadiazole synthetic methods have been developed.…”
Section: Introductionmentioning
confidence: 99%